DINAMIKA INTERAKSI SANTRI TAHFIDZ DAN SISWA FORMAL DALAM LEMBAGA PENDIDIKAN ISLAM (STUDI KASUS DI MADRASAH TSANAWIYAH SWASTA DARUL IHSAN WAWONGGURA) - Erna Mudrikah; Ismail; Basrin Melamba (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This article discusses the dynamics of interaction between tahfidz students and formal students at Darul Ihsan Wawonggura Private Middle School. This study aims to understand how this interaction affects the learning process and character development of both groups of students. Using qualitative methods, data were collected through interviews, observations, and documentation studies. The results of the study indicate that there is a positive synergy between tahfidz students who focus on memorizing the Qur'an and formal students who follow the general curriculum. This interaction not only increases learning motivation but also strengthens spiritual and social values ​​among students. In addition, the results of the study also show that the interaction between tahfidz students and formal students not only enriches the learning experience but also creates an atmosphere of mutual respect and support between the two groups. These findings are expected to contribute to the development of a more integrative education model in Islamic educational institutions